Low RUNX3 expression alters dendritic cell function in patients with systemic sclerosis and contributes to enhanced fibrosis. Issue 9 (24th September 2019) - Affandi, Alsya J; Carvalheiro, Tiago; Ottria, Andrea; Broen, Jasper CA; Bossini-Castillo, Lara; Tieland, Ralph G; Bon, Lenny van; Chouri, Eleni; Rossato, Marzia; Mertens, Jorre S; Garcia, Samuel; Pandit, Aridaman; et al.
Abstract : Objectives: Systemic sclerosis (SSc) is an autoimmune disease with unknown pathogenesis manifested by inflammation, vasculopathy and fibrosis in skin and internal organs. Type I interferon signature found in SSc propelled us to study plasmacytoid dendritic cells (pDCs) in this disease. We aimed to identify candidate pathways underlying pDC aberrancies in SSc and to validate its function on pDC biology. Methods: In total, 1193 patients with SSc were compared with 1387 healthy donors and 8 patients with localised scleroderma. PCR-based transcription factor profiling and methylation status analyses, single nucleotide polymorphism genotyping by sequencing and flow cytometry analysis were performed in pDCs isolated from the circulation of healthy controls or patients with SSc. pDCs were also cultured under hypoxia, inhibitors of methylation and hypoxia-inducible factors and runt-related transcription factor 3 (RUNX3) levels were determined. To study Runx3 function, Itgax -Cre: Runx3 f/f mice were used in in vitro functional assay and bleomycin-induced SSc skin inflammation and fibrosis model. Results: Here, we show downregulation of transcription factor RUNX3 in SSc pDCs. A higher methylation status of the RUNX3 gene, which is associated with polymorphism rs6672420, correlates with lower RUNX3 expression and SSc susceptibility. Hypoxia is another factor that decreases RUNX3 level in pDC. Mouse pDCs deficient of Runx3 show enhanced maturation markers on CpG stimulation. In vivo, deletion of Runx3 in dendritic cell leads to spontaneous induction of skin fibrosis in untreated mice and increased severity of bleomycin-induced skin fibrosis. Conclusions: We show at least two pathways potentially causing low RUNX3 level in SSc pDCs, and we demonstrate the detrimental effect of loss of Runx3 in SSc model further underscoring the role of pDCs in this disease.